Incidencia de complicaciones agudas en fracturas supracondileas en pacientes pediátricos atendidos en el Hospital Regional de Loreto desde enero 2021 a diciembre 2021 - Bernaola Zevallos, Juan Ramón (2022)
Supracondylar humerus fractures are the most common fractures in children and the second fracture in frequency of all the fractures in children1-2. According to Cheng et al (1999), supracondylar humerus fractures account for about 10% of all the pediatric fractures. Distal Radial fractures are the most common and they account for about 20% of all pediatric fractures. In this age group, supracondylar fractures account for 27 and 32% of all the fractures, respectively2. Supracondylar humerus fractures are most common in children aged 4-8 years old3.4. This fracture carries important functional loss in children, for this reason, the objective of this investigation project will be acute complications and its conservative or surgical treatment. Objective. To determine the incidence of acute complications in children with supracondylar humerus fractures, admitted to the Orthopedic Surgery Service at the Hospital Regional of Loreto from January to December 2021. Method: The present project is an observational, descriptive and transversal investigation with a sample of 100 children with supracondylar fractures admitted to the Orthopedic Surgery Service at the Hospital Regional of Loreto from January to December 2021.